Molecular detection of pathogens from ectoparasites recovered from peri-domestic animals, and the first description of a Candidatus Midichloria sp. from Haemaphysalis wellingtoni from rural communities in Malaysia. (February 2021) - Khoo, Jing Jing; Husin, Nurul Aini; Lim, Fang Shiang; Oslan, Siti Nur Hazwani; Mohd Azami, Siti Nurul Izzah; To, Soon Wei; Abd Majid, Mohamad Azlan; Lee, Hai Yen; Loong, Shih Keng; Khor, Chee Sieng; AbuBakar, Sazaly
Abstract: Rural communities in Malaysia have been shown to be exposed to Coxiella, Borrelia and rickettsial infections in previous seroprevalence studies. Further research is necessary to identify the actual causative agents and the potential vectors of these infections. The arthropods parasitizing peri-domestic animals in these communities may serve as the vector in transmitting arthropod-borne and zoonotic agents to the humans. Molecular screening of bacterial and zoonotic pathogens from ticks and fleas collected from dogs, cats and chickens from six rural communities in Malaysia was undertaken. These communities were made up of mainly the indigenous people of Malaysia, known as the Orang Asli, as well as settlers in oil palm plantations. The presence of Coxiella burnetii, Borrelia, and rickettsial agents, including Rickettsia and Anaplasma, was investigated by performing polymerase chain reaction (PCR) and DNA sequencing. Candidatus Rickettsia senegalensis was detected in one out of eight pools of Ctenocephalides felis fleas. A relapsing fever group Borrelia sp. was identified from one of seven Haemaphysalis hystricis ticks tested. The results from the PCR screening for Anaplasma unexpectedly revealed the presence of Candidatus Midichloria sp., a potential tick endosymbiont, in two out of fourteen Haemaphysalis wellingtoni ticks tested. C. burnetii was not detected in any of the samples tested. The findings here provide evidence for the presence of potentially novel strains of rickettsial and borrelial agents in which their impact on public health risks among the rural communities in Malaysia merit further investigation. The detection of a potential endosymbiont of ticks also suggest that the presence of tick endosymbionts in the region is not fully explored. Graphical abstract: Unlabelled Image